High basal expression of interferon-stimulated genes in human bronchial epithelial (BEAS-2B) cells contributes to influenza A virus resistance - Seng, Lai-Giea; Daly, Janet M.; Chang, Kin-Chow; Kuchipudi, Suresh V. (Public Library of Science, 2014)
Respiratory epithelial cells play a key role in influenza A virus (IAV) pathogenesis and host innate response. Transformed human respiratory cell lines are widely used in the study of IAV−host interactions due to their relative convenience, and inherent difficulties in working with primary cells. Transformed cells, however, may have altered susceptibility to virus infection. Proper characterization of different respiratory cell types in their responses to IAV infection is therefore needed to ensure that the cell line chosen will provide results that are of relevance in vivo. We compared replication kinetics of human H1N1 (A/USSR/77) IAVs in normal primary human bronchial epithelial (NHBE) and two commonly used respiratory epithelial cell lines namely BEAS-2B and A549 cells. We found that IAV replication was distinctly poor in BEAS-2B cells in comparison with NHBE, A549 and Madin-Darby canine kidney (MDCK) cells. IAV resistance in BEAS-2B cells was accompanied by an activated antiviral state with high basal expression of interferon (IFN) regulatory factor-7 (IRF-7), stimulator of IFN genes (STING) and IFN stimulated genes (ISGs). Treatment of BEAS-2B cells with a pan-Janus-activated-kinase (JAK) inhibitor decreased IRF-7 and ISG expression and resulted in increased IAV replication. Therefore, the use of highly resistant BEAS-2B cells in IAV infection may not reflect the cytopathogenicity of IAV in human epithelial cells in vivo.